Zagadnienie Lepkosprężystego Pręta Kołowego na Podłożu Lepkosprężystym - Skalmierski, B. (Engineering Transactions, 1965)
The bar under consideration is a viscoelastic circularly curved bar of small curvature and simply connected cross-section, resting on a viscoelastic foundation. It is assumed that it is loaded by radial forces only. The problem is considered as a quasi-static and dynamic problem (the inertia forces being included). The results are obtained as an inverse Laplace and Fourier transform. In conclusion is considered the time-dependency of the deflection under the action of a wandering radial force. The Voigt body is assumed for detailed considerations.